Physical and Mechanical Properties of Palm Oil Frond and Stem Bunch for Developing Pruner and Harvester Machinery Design - Yazid Ismi Intara; Hamdi Mayulu; P.A.S. Radite (International Journal of Science and Engineering, 2013)
A development of oil palm pruner and harvester machinery design implemented in the field still faces a problem due to the lack of effective and efficient design which is need to be solved. It was noted that in order to develop the design, an early data and information of physical and mechanical properties of palm oil frond and stem fruits is critically important. The objective of the research was to obtain the physical and mechanical properties of palm oil frond and stem in order to develop the design of pruner and harvester machinery. The result showed that tool machinery was been advantageous by the physical properties of the plant i.e. the total weight of frond and leaf which enable to support the cutting process. The average of total weight of frond and leaf was 16.8 kg. The diagonal cutting trajectory was been more advantageous because of total weight and frond shape toward to the different of the plant tissue area. The measurement result shows that cutting curve follows the time required for cutting. The comparison among cutting curve shows differences in cutting thickness or length. In this case, the thickness is linear with cutting time. Besides, those curves show differences at the height which determine the maximum value of tested material cutting resistance. Alternative solution for machinery development design is pruner-harvester for height plant below 6 m and among 6 to 12 m. For below 6 m, pruner-harvester was designed by incorporating motor as power source and cutter-disc as the knife cutter. That condition was relied on that estate which was maintenance intensively commonly used cutter-disc. Pruner-harvester above 6 m and up to 12 m was improved based on manual egrek-designed by adding fresh fruit bunch alley supply glide in order to keep the fruits still in intact form. The consideration was based on affectivity and efficiency. It also considers homogenous ecological of palm oil plant which should be maintained to reduce global warming effect. Information obtained in this research could become positive consideration and alternative solution to provide problem solvingat early development design of palm oil pruner and harvester machinery.Doi: http://dx.doi.org/10.12777/ijse.4.2.2013.69-74[How to cite this article: Intara, Y.I., Mayulu, H., and Radite, P.A.S. (2013). Physical and Mechanical Properties of Palm Oil Frond and Stem Bunch for Developing Pruner and Harvester Machinery Design. International Journal of Science and Engineering, 4(2),69-74. Doi: http://dx.doi.org/10.12777/ijse.4.2.2013.69-74]